2022
DOI: 10.3390/ijms23105653
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Set Enrichment Profiles in Eosinophilic and Non-Eosinophilic Chronic Rhinosinusitis with Nasal Polyps by Bulk RNA Barcoding and Sequencing

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease with a high symptom burden, including nasal congestion and smell disorders. This study performed a detailed transcriptomic analysis in CRSwNP classified as eosinophilic CRS (ECRS), nonECRS according to the Japanese Epidemiological Survey of Refractory Eosinophilic Chronic Rhinosinusitis (JESREC) criteria, and a group of ECRS with comorbid aspirin intolerant asthma (Asp). Gene expression profiles of nasal polyps and the uncinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Asthma is a heterogeneous pulmonary disease comprised of several different endotypes which depict various pathways of the inflammatory and immune response 38 . In general, most of the current research concentrates on eosinophilic airway inflammation, with poor knowledge of principal causes and mechanisms related to non-eosinophilic phenotypes, which are less receptive to inhaled corticosteroids (ICS), the current treatment of choice for asthma 39 - 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a heterogeneous pulmonary disease comprised of several different endotypes which depict various pathways of the inflammatory and immune response 38 . In general, most of the current research concentrates on eosinophilic airway inflammation, with poor knowledge of principal causes and mechanisms related to non-eosinophilic phenotypes, which are less receptive to inhaled corticosteroids (ICS), the current treatment of choice for asthma 39 - 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a heterogeneous pulmonary disease comprised of several different endotypes which depict various pathways of the inflammatory and immune response [38]. In general, most of the current research concentrates on eosinophilic airway inflammation, with poor knowledge of principal causes and mechanisms related to non-eosinophilic phenotypes, which are less receptive to inhaled corticosteroids (ICS), the current treatment of choice for asthma [39][40][41]. In the present study, we demonstrated that sphingolipid metabolism is abnormal in asthmatic patients, whereas sphingosine metabolites, altered largely in the untargeted lipidomics analysis, failed to distinguish between the different endotypes of asthma both in plasma and induced sputum in the targeted lipidomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically among DEGs detected in EoD compared to controls, within CD4 + T there was an upregulation of genes associated with the chronic rhinosinusitis and nasal polyps ( SCGB3A1 and MTRNR2L8 ) (61, 62), and downregulation of IL27RA , whose decreased expression is associated with allergic airway inflammation (63). Within DC cells, there was also dysregulation of genes associated with chronic obstructive pulmonary disorder (COPD) ( LILRA5, IGLC2 , and IGLC3 ) (64, 65).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from the same NPs biopsies and RNA-Seq was performed using Illumina HiSeq4000, as described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%